Risk Factors for Different Types of Pregnancy Losses: Analysis of 15,210 Pregnancies After Embryo Transfer - Yang, Ai-Min; Xu, Xiuhua; Han, Yan; Wei, Jian-Jun; Hao, Gui-Min; Cui, Na; Zhao, Zhi-Ming; Wang, Wei; Huang, Xianghua (Frontiers in Endocrinology, 2021)
Objective To evaluate the risk factors for different types of pregnancy losses after embryo transfer (ET). Design Retrospective cohort study. Setting Reproductive medicine center. Participants A total of 15,210 pregnancies after fresh and frozen-thawed embryo transfer between January 2014 and June 2019. Main Outcome Measures The primary outcome was pregnancy loss (PL) throughout the entire pregnancy. Secondary outcomes were non-visualized PL, early miscarriage, late miscarriage, and stillbirth. Methods The effect of patients’ baseline characteristics and IVF/ICSI cycle-specific factors on the risk of PL after fresh and frozen-thawed ET was determined by multivariate logistic regression analysis. Results Compared to women under 35 years old, those between 35 and 40 had an increased risk of early miscarriage [odds ratio (OR) 1.49, 95% confidence interval (CI) 1.22-1.83], while those after 40 appeared to have an increased risk of both early miscarriage (OR 3.82, 95% CI 2.65-5.51) and late miscarriage (OR 2.79, 95% CI 1.64-4.77). Overweight patients were observed to have a higher risk of late miscarriage (OR 1.38, 95% CI 1.16-1.65), while obese patients showed a higher risk of both early miscarriage (OR 1.47, 95% CI 1.14-1.91) and late miscarriage (OR 1.80, 95% CI 1.33-2.44). Polycystic ovary syndrome (PCOS) was an independent risk factor for late miscarriage (OR 1.58, 95% CI 1.28-1.96), and the detrimental effect of PCOS was independent of obesity status. Women with uterine factors had a higher risk of early miscarriage (OR 1.77 (95% CI 1.32-2.38) than women without uterine factors. A negative correlation was observed between the thickness of the endometrium and PL (OR 0.95 95% CI 0.92-0.97). There was an increased risk of PL after frozen-thawed ET versus fresh ET (OR 1.12, 95% CI 1.01-1.24). Women who transferred ≥2 embryos showed lower risk of overall PL than women who transferred a single embryo, with adjusted ORs ranged from 0.57 0.94. However, women who transferred three embryos demonstrated a higher risk of late miscarriage than women who transferred a single embryo (OR 2.23, 95% CI 1.36-3.66). Conclusions Patients with uterine factors demonstrated higher risk of early miscarriage and stillbirth. Being overweight, PCOS, and transferring three embryos was associated with late miscarriage. Being aged 40 and over, obese, and using frozen embryo transfer was associated with early and late miscarriage.